Library Facilities and Students' Intention to Visit For Information Seeking at an Indonesian Aviation Academy - Safitri Era Globalisasi; Nafana Aulia Rochida; Dede Ardian; Hendra Sudarso; Tutus Iggi Saphara (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
Academic libraries remain important learning and information environments, yet the attractiveness of a library depends partly on whether its facilities match users' academic and non-academic information needs. This study examines the effect of library facilities on students' intention to visit the library at the Indonesian Aviation Academy Banyuwangi. A quantitative descriptive design was applied to the entire population of 98 students using census sampling. Data were collected through a four-point Likert questionnaire and analyzed with validity and reliability tests, descriptive statistics, simple linear regression, and a partial t-test using IBM SPSS Statistics 26. The instruments were reliable, with Cronbach's alpha values of 0.951 for library facilities and 0.957 for visit intention. The regression equation was Y = 9.549 + 0.523X. Library facilities had a positive and statistically significant effect on visit intention (t = 5.883; p < .001). The findings indicate that comfortable learning spaces, relevant collections, supporting infrastructure, and accessible services can strengthen students' willingness to use the library for academic and non-academic information seeking. The academy should therefore prioritize sustained improvement of facilities and collections while maintaining user-oriented services.